2022
DOI: 10.1177/00302228221087505
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Nurses’ Anxiety About COVID-19, Approaches to and Attitudes Toward Dying with Dignity Principles During the Pandemic

Abstract: While trying to protect themselves from COVID-19, intensive care nurses saved many patients by providing care during the pandemic. The aim of this study is to determine the anxiety levels of nurses working in intensive care units about COVID-19, attitudes toward and approaches to end-of-life care, and attitudes toward dying with dignity. This cross-sectional descriptive study was carried out with 144 nurses. The Attitudes and Behaviors of ICU Nurses Intended for End-of-Life Care Scale, Attitudes towards Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Erzincanlı and Sayın Kasar 27 found that nurses' attitude and behaviors to EOL care mean scores did not show a significant difference according to age and intensive care experience. Can Özdemir et al 28 found that the attitude to EOL care was more positive in female (3.45 ± 0.52) than in male participants (3.03 ± 0.69). In contrast to these findings, it was found in the present study that the mean scores on attitude and behaviors to EOL care were better in male than in female participants.…”
Section: Discussionmentioning
confidence: 98%
“…Erzincanlı and Sayın Kasar 27 found that nurses' attitude and behaviors to EOL care mean scores did not show a significant difference according to age and intensive care experience. Can Özdemir et al 28 found that the attitude to EOL care was more positive in female (3.45 ± 0.52) than in male participants (3.03 ± 0.69). In contrast to these findings, it was found in the present study that the mean scores on attitude and behaviors to EOL care were better in male than in female participants.…”
Section: Discussionmentioning
confidence: 98%
“…Salud sexual 75,77,78,87 Satisfacción laboral 63,122 Sexualidad 75,76,77,78,79,80,81,82,83,84,85,86,87,88 T Tabú 75,76,85 Terapia ocupacional 147,161,165,180,181,182 Toxicología 57,59 Transmisión 31,36,38,48,86 Trichomonas vaginalis 31,32,38,39,40,41,42,43 Trypanosoma cruzi 31,32,35,40,41,42,43 V Vínculo terapéutico 160,161,168,170,173,176,177,178,180,181,182…”
Section: íNdice Remissivomentioning
confidence: 99%